Eighth International Symposium on Wearable Computers
DOI: 10.1109/iswc.2004.6
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction System for Watch Computers Using Tactile Guidance and Bidirectional Segmented Strokes

Abstract: We introduce an input system that is based on bidirectional strokes that are segmented by tactile landmarks. By giving the user tactile feedback about the length of a stroke during input, we decrease the dependence of the GUI on the visual display. By concatenating separate strokes into multi-strokes, complex commands may be entered, which may encode commands, data content, or both simultaneously. To demonstrate their power, we show how multi-strokes can be used to traverse a menu hierarchy quickly. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…systems like the Zypad, "WatchPad", etc. to name a few [5], [6], [7], [8]), but have not addressed vibro-tactile stimulation for non-disruptive communication up until now. [9] generally addresses user distraction as a factor which may mask or obscure vibrotactile perception.…”
Section: Introductionmentioning
confidence: 99%
“…systems like the Zypad, "WatchPad", etc. to name a few [5], [6], [7], [8]), but have not addressed vibro-tactile stimulation for non-disruptive communication up until now. [9] generally addresses user distraction as a factor which may mask or obscure vibrotactile perception.…”
Section: Introductionmentioning
confidence: 99%
“…Parameter adjustment by circular sliders in combination with passive haptic feedback provided by a physical input device can be also found in the watch computer interaction system of Blaskó and Feiner [1] as well as in some commodity computer devices like the iPod TM scroll wheel. Empirical comparison of such touch-based interfaces with tactile guidance to physical scroll wheels [24] and jog dials [15] revealed that the semi-tangible approach is not necessarily worse in terms of task performance.…”
Section: Tangible Constraintsmentioning
confidence: 99%
“…We chose to employ the multiwidget [5]. The multiwidget allows a single touch sensor (e.g., a touchscreen or a section of a capacitive touchpad) to virtually implement a multitude of directly accessible cursorless manipulator widgets, with the assistance of passive haptic feedback.…”
Section: Multiwidget-based Interactionsmentioning
confidence: 99%
“…We then discuss simple content-manipulation techniques controlled by the orientation and position of the user's wrist, which we implemented with our simulator. Finally, we discuss how cursorless interaction methods [5] can keep users from having to look away from the projected display, and show how these methods can be applied to manipulate content and control a prototype stock market information browser application.…”
Section: Introductionmentioning
confidence: 99%